1988
DOI: 10.3758/bf03202701
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring animals’ movements using digitized video images

Abstract: An animal's movements can be monitored continuously using video digitization techniques. We outline the differences between video frame-grabbers and column-scan digitizers, and describe two applications using column-scanners: detecting episodes of spontaneous locomotionand tracking the position of a moving appendage. Strategies are discussed for increasing the speed of software and for compressing the information in the video images into an analog motion signal to be displayed and stored for later analysis. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…The first video digitizers were of the column scan type. These had no internal memory of their own and were able to sample the video signal only at rather low rates (Olivo & Thompson, 1988). In contrast, a modern frame grabber uses a high-speed analog-to-digital converter to enable real-time conversion of the entire video image to a high-resolution grid of pixels.…”
Section: Video Trackingmentioning
confidence: 99%
“…The first video digitizers were of the column scan type. These had no internal memory of their own and were able to sample the video signal only at rather low rates (Olivo & Thompson, 1988). In contrast, a modern frame grabber uses a high-speed analog-to-digital converter to enable real-time conversion of the entire video image to a high-resolution grid of pixels.…”
Section: Video Trackingmentioning
confidence: 99%
“…These had no internal memory of their own, and were only able to sample the video signal at rather low rates [23]. In contrast, a modern frame grabber uses a high-speed analogdigital converter to enable real time conversion of the entire video image to a high-resolution grid of pixels [23].…”
Section: The Development Of Automated Observation Systemsmentioning
confidence: 99%
“…In much research, through distinct objectives, movements and activities of animals have been observed and measured (Fraser, 1978;Olivo and Thompson, 1988;Schofield, 1993;Brandl, 1997). In these studies, a first possibility involves looking at the animals and noting their behaviour.…”
Section: Introductionmentioning
confidence: 99%